2023
DOI: 10.21203/rs.3.rs-2663599/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the ameliorative role of Equisetum diffusum D. Don whole-plant methanolic-extract in acute inflammation and molecular docking analysis of GC-MS-identified phytocompounds with few prominent inflammatory markers/cytokines for inspecting the potent drug targets.

Abstract: Equisetum diffusum D. Don (Fam. Equisetaceae), commonly known as ‘Himalayan horsetail’ is an important medicinal pteridophyte species having various ethnobotanical properties; and traditionally been used in the treatment of back pain, bone fracture, bone dislocation, and arthritis by various tribal communities of India. Although the pharmacological uses are known, no study related to its ethnobotanical validation in experimental animal models has been reported till date. The goal of the present study was to va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Using GC-MS analysis, it is reported that ED extracts contain tens of potent bioactive compounds, including mainly phenolics, avonoids, saponin and tannin. 33,34 These phytocompounds are recognized to bind effectively with metal ions through their multiple functional groups. Thus, they are efficient in stabilizing AgNPs and are also desired for the selective detection of specic metal ions in water samples, as will be discussed below.…”
Section: Characterization Of the Synthesized Ed-agnpsmentioning
confidence: 99%
“…Using GC-MS analysis, it is reported that ED extracts contain tens of potent bioactive compounds, including mainly phenolics, avonoids, saponin and tannin. 33,34 These phytocompounds are recognized to bind effectively with metal ions through their multiple functional groups. Thus, they are efficient in stabilizing AgNPs and are also desired for the selective detection of specic metal ions in water samples, as will be discussed below.…”
Section: Characterization Of the Synthesized Ed-agnpsmentioning
confidence: 99%